Effect of tobacco use on semen in infertile male - Sujata R Kanetkar; Sushant Mohite; Rohit S Kadam; Nilesh Gupta; Chirag R Vadhel (Wolters Kluwer Medknow Publications, 2024)
Background/Objective/Methods: Infertility is one of the major global public health issues. In a social setup like India, there is a strong emphasis on childbearing, which leads to economic and psychological stress and trauma. Various studies have shown that worldwide, there is a decline in the quality of semen. Many environmental, nutritional, and lifestyle factors are responsible for the reduced semen quality. The methods of this study are the source of data, the method of collection of data, and statistical analysis. Results: Semen analysis is an important diagnostic test in the assessment of infertility in male partners. Ninety-eight semen samples were analyzed from the patients who presented with the complaint of infertility over a period of 2 years (June 2018-May 2020). Conclusion: Based on our analysis, it can be inferred that an escalation in the intensity of tobacco consumption is directly associated with a proportional decline in sperm count and motility and a notable increase in liquefaction time.